ANALYZING THE IMPACT OF PRICE POLICY ON WHEAT PRODUCTION IN IRAQ BY USING POLICY ANALYSIS MATRIX (PAM) - & MUDHI, MOHAMMED (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The objectives of this study are to analyses the impact of price policy on wheat production in Iraq through its efficiency in resource allocation using Policy Analysis Matrix (PAM) technique. This study depends basically on primary data collected from a random sample consisted of 115 farms, The sample has been divided into three subclasses, the first one area was less than 50 donum consisted of 64 farms, the second one area was between 50 – 100 donum and consisted of 33 farm, the third one area was more than 100 donum and consisted of 18 farm. The objective of this study is to analyses the impact of price policy on wheat production in Iraq. By estimation of policy analysis matrix elements, revenue transfers, tradable input transfers, factors transfers, were calculated which were revenue (654,584,455,553) and (348, 357, 275, 339) thousand dinars/donum in private and social price to three classes and the sample total consecutively, tradable input  (100,107,112,104) and (76,86,87,79) thousand dinars/donum in private and social price to three classes and the sample total consecutively, factors (254,211,177,230) and (260, 214,179,234) thousand dinars/donum in private and social price to three classes and the sample total consecutively, Net transfer was about (197,209,158,193) thousand dinars/donum to three classes and the sample total consecutively. The results of this study showed that the price policy used by government was encouraging producers in short run and also showed that wheat production had large support from government while inputs were not subsidized, the study also showed that private profits were more than social profits. Results also showed that wheat production in Iraq has a comparative advantage and internationally competitive. Finally the study arrived at some conclusions and recommendations according to conclusion.